1996
DOI: 10.1007/bf00196578
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion receptors in malignant transformation and dissemination of gastrointestinal tumors

Abstract: Changes in the expression and function of adhesion molecules on the surface of cancer cells are important characteristics in the development of gastrointestinal malignancies and might be used in the future as prognostic factors or as new targets for diagnostic and therapeutic approaches. In esophageal cancer a down-regulation of the E-cadherin receptor and the cytoplasmic protein alpha-catenin is associated with tumor dedifferentiation, infiltrative growth and lymph-node metastasis. In gastric cancer a reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 0 publications
0
16
0
2
Order By: Relevance
“…Thus, the basal membrane and the ECM jointly represent two important physical barriers to malignant invasion, and their degradation by metalloproteinase enzymes may have an important role in tumor progression and metastatic dissemination [2–4]. Other researchers, however, have reported that, in general, the expression levels of integrins alpha 3 and alpha 5 are reduced in many colorectal carcinomas (CRCs) [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus, the basal membrane and the ECM jointly represent two important physical barriers to malignant invasion, and their degradation by metalloproteinase enzymes may have an important role in tumor progression and metastatic dissemination [2–4]. Other researchers, however, have reported that, in general, the expression levels of integrins alpha 3 and alpha 5 are reduced in many colorectal carcinomas (CRCs) [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, numerous researchers, including ourselves, have analysed diuse and adhesive-type tumours in order to ®nd dierences in the expression or integrity of cell adhesion molecules, especially E-cadherin (cf. Gabbert et al, 1996;Streit et al, 1996, for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have suggested that expression of certain adhesion molecules by the tumour cells could predetermine their affinity for the CNS 8 , 9. For example, some variant forms of CD44 are preferentially expressed by brain metastases from colon or lung lesions than by primary brain tumours 10…”
Section: Discussionmentioning
confidence: 99%